2017
DOI: 10.1016/j.bbmt.2017.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Association of Plasma CD163 Concentration with De Novo–Onset Chronic Graft-versus-Host Disease

Abstract: Chronic graft-versus-host disease (cGVHD) is the leading cause of long-term morbidity and mortality after allogeneic hematopoietic cell transplantation. In order to identify prognostic plasma proteins associated with de novo or quiescent-onset cGVHD, we performed a discovery and validation proteomic study. The total study cohort included 167 consecutive patients who had no clinical evidence of GVHD under minimum glucocorticoid administration, and had available plasma samples obtained at 80±14 days after transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…For this reason, it is important that we establish clinical laboratory parameters that can be used to follow the response to ECP. In the past 5 years, several biomarkers emerged as useful predictors of chronic GvHD onset, severity, and therapy refractoriness; notably, suppression of tumorigenicity 2 (ST2), matrix metalloproteinase‐3 (MMP3), chemokine (C‐X‐C motif) ligand 9 (CXCL9), CXCL10, CXCL11, CD163, and B‐cell activating factor (BAFF) . In an effort to explore previously established chronic GvHD biomarkers in the context of ECP, we conducted a proof‐of‐principle study wherein clinical characteristics were systematically captured and serum was collected before ECP and at 2‐month intervals for 6 months for the purpose of biomarker testing.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, it is important that we establish clinical laboratory parameters that can be used to follow the response to ECP. In the past 5 years, several biomarkers emerged as useful predictors of chronic GvHD onset, severity, and therapy refractoriness; notably, suppression of tumorigenicity 2 (ST2), matrix metalloproteinase‐3 (MMP3), chemokine (C‐X‐C motif) ligand 9 (CXCL9), CXCL10, CXCL11, CD163, and B‐cell activating factor (BAFF) . In an effort to explore previously established chronic GvHD biomarkers in the context of ECP, we conducted a proof‐of‐principle study wherein clinical characteristics were systematically captured and serum was collected before ECP and at 2‐month intervals for 6 months for the purpose of biomarker testing.…”
Section: Introductionmentioning
confidence: 99%
“…CD163 is a macrophage scavenger receptor elevated in oxidative conditions [52]. The cumulative incidence of de novo- onset cGVHD was higher in patients with higher plasma soluble CD163 concentrations at day 80 than those with lower concentrations.…”
Section: Useful Cgvhd Biomarkersmentioning
confidence: 99%
“…The cumulative incidence of de novo- onset cGVHD was higher in patients with higher plasma soluble CD163 concentrations at day 80 than those with lower concentrations. The group suggested that monocyte or macrophage activation or increased oxidative stress may contribute to the pathogenesis of cGVHD [52]. …”
Section: Useful Cgvhd Biomarkersmentioning
confidence: 99%
“…Altogether, the IFN‐inducible chemokines CXCL9 and CXCL10, responsible for CXCR3 expressing Th1/NK lymphocyte recruitment into tissues, are upregulated at diagnosis and are worth being pursued and tested in prospectively collected samples. Plasma CD163 concentration has been associated with de novo‐onset cGVHD . Using a combination of flow and mass cytometry, it was shown that patients with more severe cGVHD had lower mucosal‐associated T cell frequencies, with a concomitant higher level of CD38 expression on T cells .…”
Section: Recent Validated Post‐transplantation Markersmentioning
confidence: 99%